The Effectiveness of Use of Multimodal Text Teaching Materials on Learning the Indonesian Language in High School - Firdaus, Septian; Komarudin; Gloriani, Yusida (PT Inovasi Pratama Internasional, 2024)
Currently, in the digital era, the use of technology in learning is becoming increasingly more important. Multimodal texts, which combine various modes of communication such as text, images, audio, and video, are used as interesting texts in learning Indonesian. This research aims to determine the effectiveness of using multimodal text teaching materials in Indonesian language learning in high school. This type of research is experimental quantitative research; the approach used is scientific. The data source in this research is Multimodal text teaching materials. The data in this research is in the form of pretest and posttest. Data collection techniques in this research used observation, tests, and documentation. The data analysis used in this research is descriptive statistical analysis and gain index data analysis. The sig value is shown in the data processing results using the independent t-test. (2-tailed) is 0.025<0.05. So Ho is rejected, and Ha is accepted, so there is a significant average difference between the experimental class and the control class. There are findings of multimodal text forms in the e-book module. Multimodal learning is an effective medium used to increase understanding in high school students.